TEACHER TALK TIME IN ENGLISH CLASSROOM - Aprilia Handayani; Amalul Umam (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2017)
Classroom interaction is described as a communication process between teacher and students that involves talk as a tool to achieve good communication. Talk is essential to students thinking and learning, and their productive engagement in classroom. This study will figure out TTT phenomenon. The aim of to the study is to explore kind of teacher talk used by English teachers and students? perception toward it. An English teacher and 33 junior high school students are the participants of the study. They are given a questionnaire that consist 15 statements. Observation and Interview are conducted to complete the data collection. The result shows that TTT is important in ELT classroom and students have positive positive perception toward it.